CHARACTERISTICS OF THE BIOLOGICAL, PSYCHOSOCIAL AND PRODUCTION FACTORS PSYCHOGENESIS PATHOLOGICAL REACTIONS AND CONDITION AMONG THE PEOPLE ORGANIZED INDUSTRIAL POPULATION - Підлубний В. Л., (World of Medicine and Biology, 2015)
Described and analyzed the results of a comprehensive assessment of maladjustment industrial workers. Summarizes the biopsychosocial accents depending on length of service, type of work, age, gender features. Presented accents risk, as well as the development of maladjustment in the presence of somatic diseases. On the basis of data provided a modus psychoprophylaxis and psychotherapeutic support in order to minimize factors that violate the adaptation among the organized industrial population.
Keywords: industrial population; psychogenesis; psychological maladjustment; risk factors; therapy; psychoprophylaxis